Competing Mortality in Patients With Neuroendocrine Tumors. (August 2019) - Low, Soon Khai; Giannis, Dimitrios; Bahaie, Nourelhoda Sami; Trong, Bao Long Hoang; Moris, Dimitrios; Huy, Nguyen Tien
Abstract : Objectives: Patients with neuroendocrine tumors (NETs) are at increased risk of mortality from competing causes in light of the improvement in overall survival over recent decades. The purpose of this study was to explore the competing causes of deaths and the risk factors associated with competing mortality. Materials and Methods: The Surveillance, Epidemiology, and End Results database was used to identify patients diagnosed with NETs between 1973 and 2015. Risk of competing mortality was estimated by the standardized mortality ratios (SMRs) and by using the Fine and Gray multivariate regression model. Results: Of the 29, 981 NET patients, 42.5% of the deaths that occurred during follow-up were attributed to competing causes (83.9% from noncancer causes and 16.1% from second primary neoplasms). Overall SMR of competing mortality was 2.50 (95% confidence interval [CI]: 2.43-2.56). The SMR of noncancer causes was 2.65 (95% CI: 2.58-2.73), with the highest risk present within the first year of diagnosis. The SMR of second primary neoplasms was 1.91 (95% CI: 1.79-2.04), with the highest risk observed after 10-year postdiagnosis. A drastic rise in competing mortality was observed in the last decade between 2005 and 2015. Advanced age, black race, small intestinal and gastric NETs, and surgery were significantly associated with competing mortality. Female, pancreatic and recto-anal NETs, distant and regional spread, chemotherapy and radiotherapy were significantly associated with lower competing mortality. Conclusions: Competing mortality plays an increasingly significant role over the years and may hamper efforts made to improve survival outcomes in NET patients. Abstract : Supplemental Digital Content is available in the text.